Estrogen-induced FXR1 promotes endocrine resistance and bone metastasis in breast cancer via BCL2 and GPX4 - Shang, Yinzhong; Cao, Tingfang; Ma, Xin; Huang, Le; Wu, Mingming; Xu, Junchao; Wang, Jiarui; Wang, Hao; Wu, Sheng; Pandey, Vijay; Wu, Zhengsheng; Zhang, Weijie; et al. (Frontiers in Cell and Developmental Biology, 2025)
Estrogen signaling dysregulation plays a critical role in the development of anti-estrogen resistance and bone metastasis of ER+ mammary carcinoma. Using quantitative proteomic screening, we identified FXR1 as an estrogen-regulated RNA-binding protein associated with anti-estrogen resistance. Mechanistically, estrogen and IGF1 facilitate FXR1 protein translation via the PI3K/AKT/mTOR/EIF4E pathway. FXR1 enhances cellular resistance to apoptosis and ferroptosis by facilitating the maturation of BCL2 pre-mRNA and stabilizing GPX4 mRNA, respectively. Anti-estrogen resistant cells exhibit elevated FXR1 expression, and FXR1 depletion restores their sensitivity to tamoxifen. Moreover, combining FXR1 depletion with a ferroptosis inducer induces synergistic lethal in anti-estrogen resistant cells. Finally, we provide proof-of-concept evidence supporting FXR1 antagonism as a potential treatment for bone metastases in ER+ breast cancer. Our findings highlight FXR1 as a promising therapeutic target to improve existing therapeutic regimes for ER+ breast cancer patients.